2012
DOI: 10.1021/sb300014t
|View full text |Cite
|
Sign up to set email alerts
|

SCHEMA-Designed Variants of Human Arginase I and II Reveal Sequence Elements Important to Stability and Catalysis

Abstract: Arginases catalyze the divalent cation-dependent hydrolysis of L-arginine to urea and L-ornithine. There is significant interest in using arginase as a therapeutic anti-neogenic agent against L-arginine auxotrophic tumors and in enzyme replacement therapy for treating hyperargininemia. Both therapeutic applications require enzymes with sufficient stability under physiological conditions. To explore sequence elements that contribute to arginase stability we used SCHEMA-guided recombination to design a library o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 43 publications
1
52
0
Order By: Relevance
“…This suggests that each sequence/structural block behaves differently in different contexts. For certain soluble protein properties (e.g., thermostability), it has been shown that block contributions are additive, that is, context independent, and that chimera stability can be predicted using linear regression (28,29,49,50). Our data suggest that ChR localization and photocurrent properties, however, require a more complex model to account for the nonlinear dependence of function on block sequence.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…This suggests that each sequence/structural block behaves differently in different contexts. For certain soluble protein properties (e.g., thermostability), it has been shown that block contributions are additive, that is, context independent, and that chimera stability can be predicted using linear regression (28,29,49,50). Our data suggest that ChR localization and photocurrent properties, however, require a more complex model to account for the nonlinear dependence of function on block sequence.…”
Section: Resultsmentioning
confidence: 80%
“…These chimeras consist of nine blocks of one parent and a single block from one of the other two parents. An additional 103 sequences were designed to maximize mutual information (46) between chosen chimeras and the remainder of the chimeric library, using the rationale described by Romero et al (29). Seventeen of these sequences were designed with a constraint on the number of mutations from the nearest parent (<40 mutations).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study provided greater understanding about the stability in the long term of the arginase 1. The arginase 1 deactivation in physiological conditions was better understood and its possible therapeutic use in the hyperargininemia patients [44].…”
Section: Diagnosismentioning
confidence: 99%
“…Nowadays, protein engineering by directed evolution has become a standard method to tailor enzyme properties in academia and industry (mainly for biocatalysis 8 purposes). Novel application fields in material science 9 and medical science [10][11][12] will likely lead to a further growth in directed evolution reports despite that the development time for improving enzymes by directed evolution are often still too long to be implemented as a standard operation in process development. Till today most directed evolution campaigns are performed in a traditional manner, in which usually random mutagenesis libraries are generated through epPCR with low mutations frequencies (1 to 3 mutations per 1000 bp) and screened (MTP format; often 1000-2000 variants) in order to obtained improved variants.…”
Section: Introductionmentioning
confidence: 99%